Pembelajaran Berdiferensiasi dalam Upaya PeningkatanKosa Kata Peserta Didik Menggunakan Media Educandy di SMP - Maryani, Eli (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2024)
This article discusses efforts to improve students' English vocabulary mastery at SMP using the Educandy learning media. English language learning conducted so far has been limited to the use of dialogue or narrative text media, where students are asked to find the meaning of difficult words in the dictionary. This method is considered less effective in improving students' English vocabulary mastery. This study aims to describe the efforts to improve students' vocabulary using Educandy media. The research method used is classroom action research with two cycles. The results show that the use of Educandy media has proven to be effective in improving students' English vocabulary mastery. This can be seen from the increase in the average vocabulary score of students from cycle I to cycle II. Educandy is an online platform that provides various types of educational games, such as crosswords, hangman, and others. The use of Educandy media in English language learning is expected to motivate students to be more active and enthusiastic in learning vocabulary, so that they can improve their vocabulary mastery in a fun and interactive way.